Conductive silver paste for low-temperature co-fired ceramic and preparation method of conductive silver paste
By using mixed silver powder of spherical nano silver powder and sheet silver powder in the conductive silver paste for low-temperature co-fired ceramics, and combined with other ingredients, the problem of poor quality of conductive silver paste is solved, and the conductivity with high density and low resistivity is achieved, and the overall quality and reliability are improved.
Patent Information
- Application Number
- CN202510192827.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor quality of conductive silver paste for low-temperature co-fired ceramics leads to the problems of unstable performance and low reliability in electronic systems.
A mixed silver powder including spherical nano silver powder and sheet silver powder is used to combine lead-free glass powder, graphene oxide, solvents, surfactants, organic additives and thixotropic agents, and a conductive silver paste with high density and low resistivity is prepared through specific mixing and grinding processes.
The conductive properties and density of conductive silver paste are improved, the resistivity is reduced, the weather resistance and oxidation resistance are enhanced, and the overall quality of conductive silver paste for low-temperature co-fired ceramics is improved.
Smart Images

Figure CN119694628A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of conductive materials, and in particular to a conductive silver paste for low temperature co-fired ceramics and a preparation method thereof. Background Art
[0002] As a highly innovative ceramic assembly technology paradigm, co-fired ceramic technology has shown a wide range of involvement in multidisciplinary cross-fields such as electronics and circuit design, materials science, and microwave technology, and has become an important focus of interdisciplinary research. With the continuous iterative development of technology, many electronic system components and modules have shown a gradual decrease in size and weight. This trend of change has caused Low Temperature Co-fired Ceramic (LTCC) technology to arouse an increasingly strong wave of attention in the global academic and industrial circles, and its academic research value and application prospects have attracted much attention.
[0003] In the research scope of low-temperature co-fired ceramic technology, printing technology plays a pivotal role. It has a close and complex internal relationship with electronic components, conductive circuits and electronic packaging technology, and plays a fundamental supporting role in the performance, stability and reliability of the entire electronic system. Among them, conductive silver paste, as an indispensable electrode material in the field of printing technology, has become a hot topic of research in the academic community due to its key characteristics such as good conductivity and high chemical stability.
[0004] At present, conductive silver paste for low-temperature co-fired ceramics generally has the problem of poor quality.
[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0006] The purpose of the present disclosure is to provide a conductive silver paste for low temperature co-fired ceramics and a preparation method thereof, thereby overcoming the problem of poor quality of the conductive silver paste for low temperature co-fired ceramics at least to a certain extent.
[0007] According to a first aspect of the present disclosure, a conductive silver paste for low-temperature co-fired ceramics is provided, the conductive silver paste comprising the following components: mixed silver powder, lead-free glass powder, graphene oxide, solvent, surfactant, organic additive, and thixotropic agent; wherein the mixed silver powder comprises spherical nano silver powder and flaky silver powder, the mass ratio of the spherical nano silver powder to the flaky silver powder is 1:1 to 1:6, the flaky silver powder comprises a first flaky silver powder and a second flaky silver powder, the particle size of the first flaky silver powder is smaller than the particle size of the second flaky silver powder, and the weight ratio of the first flaky silver powder is greater than the weight ratio of the second flaky silver powder.
[0008] Optionally, by weight, 50 to 85 parts of silver powder, 1 to 10 parts of lead-free glass powder, 1 to 5 parts of graphene oxide, 20 to 30 parts of solvent, 0.1 to 2 parts of surfactant, 1 to 3 parts of organic additives, and 0.3 to 2 parts of thixotropic agent are mixed.
[0009] Optionally, the lead-free glass powder includes, by weight percentage, 52% to 55% SiO2, 3% to 8% Al2O3, 18% to 20% B2O3, 5% to 7% Na2O, 1% to 2% K2O, 2% to 3% ZnO, 2% to 4% BaO, 5% to 6% CaO, and 3% to 4% MgO.
[0010] Optionally, the solvent is a mixture of a polymer resin and an organic carrier, and the mass percentage of the polymer resin to the organic carrier is 2:8 to 4:6.
[0011] Optionally, the polymer resin includes one or more of ethyl cellulose, DBE, epoxy resin, vinyl resin, and polyurethane resin; the organic carrier includes one or more of pinene alcohol, ethylene glycol, and 3-methoxy-3-methylbutyl acetate.
[0012] Alternatively, the surfactant comprises sorbitan trioleate or tributyl phosphate.
[0013] Optionally, the organic additive is a mixture of a dispersant, a leveling agent and a defoaming agent, and the mass ratio of the dispersant, the leveling agent and the defoaming agent is 0.8:0.5:0.9 to 1:1:1.
[0014] Optionally, the dispersant includes one or more of sodium dodecyl sulfate, polyethylene glycol, and oleic acid; the leveling agent includes one or more of silane coupling agent, diacetone alcohol, and polymethylphenylsiloxane; and the defoamer includes modified polysiloxane or silicone defoamer.
[0015] Optionally, the thixotropic agent includes one or more of 1-methyl-2-pyrrolidone, 2-methylpyrrolidone, and fumed nano-silica.
[0016] According to a second aspect of the present disclosure, a method for preparing a conductive silver paste for low-temperature co-fired ceramics is provided, and the conductive silver paste for low-temperature co-fired ceramics is any one of the conductive silver pastes described above; wherein the preparation method comprises: mixing mixed silver powder, lead-free glass powder and solvent in a mixer to obtain a first mixture; adding graphene oxide, a surfactant, an organic additive and a thixotropic agent to the first mixture, and obtaining a second mixture after mixing; dispersing the second mixture using a high-speed disperser to obtain a third mixture; and grinding the third mixture multiple times on a three-roll mill to obtain the conductive silver paste for low-temperature co-fired ceramics.
[0017] In the scheme of the exemplary embodiment of the present disclosure, flaky silver powder with different particle size gradients is used as the main conductive phase, and a small amount of spherical nano silver powder is added. The high sintering activity of the spherical nano silver particles is used to achieve sintering between the flaky silver powders at the temperature of silver paste curing, forming a better connection structure, reducing the resistivity of the silver paste, and because the coating is dense, it is not easy to be infiltrated or permeable by the silver paste, and it has excellent weather resistance and oxidation resistance, and improves the quality of the conductive silver paste for low temperature co-fired ceramics.
[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0020] Figure 1 The flowchart of the method for preparing the conductive silver paste for low temperature co-fired ceramics according to the exemplary embodiment of the present disclosure is schematically shown.
[0021] Figure 2 The SEM (Scanning Electron Microscope) image of the silver paste after sintering in Example 1 of the present disclosure is shown.
[0022] Figure 3 The SEM image of the silver paste after sintering of Example 2 of the present disclosure is shown.
[0023] Figure 4 The SEM image of the silver paste after sintering of Example 3 of the present disclosure is shown. DETAILED DESCRIPTION
[0024] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0025] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual conditions. In addition, all the terms "first", "second", "third", etc. below are only for the purpose of distinction and should not be used as limitations of the present disclosure.
[0026] From the current research and application status, copper-based and silver-based conductive adhesives have been widely used in the field of point-to-point adhesive materials. As for copper paste, its resistivity is as low as 1.75×10 -8 Ω·m, and has excellent electron migration characteristics. At the same time, it has a relatively low cost advantage compared to other similar materials. These characteristics have attracted a lot of attention in academic research and practical application scenarios. However, it should be made clear that although copper is relatively stable and inactive in normal conditions, the surface free energy of copper atoms will increase significantly when it is in high temperature conditions. This energy change causes the tendency of copper atoms to react with oxygen in the air to rise sharply, and then quickly forms a copper oxide film under oxidation, which eventually leads to the complete loss of the conductive properties of the copper paste. Based on this physical and chemical mechanism, if copper paste is to be applied to electrode material scenarios, the conventional air sintering method obviously cannot meet the process requirements. It can only be completed with the help of an atmosphere furnace in an oxygen-free environment carefully created by inert gases such as nitrogen and argon. The corresponding sintering process. However, it cannot be ignored that this specific sintering method will inevitably raise the cost investment level of the entire preparation process, which will bring more significant economic cost pressure to large-scale industrial production, and become one of the important factors restricting its further expansion of the scope of application.
[0027] In contrast, silver is recognized as the best conductor of electrical conductivity in the field of metal conductors, with a resistivity of only about 1.65×10 -8 Ω·m, showing excellent conductive performance. In addition, silver also has excellent chemical stability, as well as excellent performance in optical and electrical properties. These unique and superior material properties have made silver the focus of academic research and practical application exploration in many disciplines. However, it must be pointed out that the high price of silver has always been like an insurmountable barrier, becoming a key bottleneck restricting its widespread application on a large scale. In view of the above reality, actively investing energy in the development of an internal electrode silver conductive paste with a relatively low conductive phase content, but which can accurately meet the strict requirements of the LTCC process in terms of multiple key indicators such as conductivity, densification and viscosity, undoubtedly has extremely important academic research value and practical application significance. This research and development direction is expected to break through the existing technical and application difficulties, open up a new path for the sustainable development of low-temperature co-fired ceramic related industries, and then promote the entire field to a higher level in academic research and engineering applications.
[0028] The disclosed embodiment provides a conductive silver paste for low-temperature co-fired ceramics with surface densification, good conductivity and low cost. The conductive silver paste includes the following components: mixed silver powder, lead-free glass powder, graphene oxide, solvent, surfactant, organic additive, and thixotropic agent. The mixed silver powder includes spherical nano silver powder and flaky silver powder, the mass ratio of spherical nano silver powder to flaky silver powder is 1:1 to 1:6, the flaky silver powder includes a first flaky silver powder and a second flaky silver powder, the particle size of the first flaky silver powder is smaller than the particle size of the second flaky silver powder, and the weight ratio of the first flaky silver powder is greater than the weight ratio of the second flaky silver powder.
[0029] The first flaky silver powder can also be referred to as flaky silver micro powder, and its particle size is 0.1 μm to 10 μm. Correspondingly, the second flaky silver powder can also be referred to as flaky silver coarse powder, and its particle size is greater than 10 μm.
[0030] Specifically, by weight, 50 to 85 parts of silver powder, 1 to 10 parts of lead-free glass powder, 1 to 5 parts of graphene oxide, 20 to 30 parts of solvent, 0.1 to 2 parts of surfactant, 1 to 3 parts of organic additives, and 0.3 to 2 parts of thixotropic agent are mixed.
[0031] In terms of weight percentage, the lead-free glass powder may include 52% to 55% SiO2, 3% to 8% Al2O3, 18% to 20% B2O3, 5% to 7% Na2O, 1% to 2% K2O, 2% to 3% ZnO, 2% to 4% BaO, 5% to 6% CaO, and 3% to 4% MgO. In addition, the thermal expansion coefficient of the lead-free glass powder is 6.02×10 -6 / K to 7.28×10 -6 / K, the sintering temperature is 820℃ to 900℃.
[0032] According to some embodiments of the present disclosure, the solvent may be a mixture of a polymer resin and an organic carrier, and the mass percentage of the polymer resin to the organic carrier is 2:8 to 4:6. The polymer resin includes one or more of ethyl cellulose, DBE (divalent acid ester), epoxy resin, vinyl resin, and polyurethane resin; the organic carrier includes one or more of terpineol, ethylene glycol, and 3-methoxy-3-methylbutyl acetate.
[0033] According to some embodiments of the present disclosure, the surfactant may include sorbitan trioleate or tributyl phosphate.
[0034] The organic additive may be a mixture of a dispersant, a leveling agent and a defoaming agent, wherein the mass ratio of the dispersant, the leveling agent and the defoaming agent is 0.8:0.5:0.9 to 1:1:1.
[0035] The dispersant may include one or more of sodium dodecyl sulfate, polyethylene glycol, and oleic acid; the leveling agent may include one or more of silane coupling agent, diacetone alcohol, and polymethylphenylsiloxane; and the defoaming agent may include modified polysiloxane or silicone defoaming agent.
[0036] The thixotropic agent may include one or more of 1-methyl-2-pyrrolidone, 2-methylpyrrolidone, and fumed nano-silica.
[0037] Reference below Figure 1 The preparation method of the conductive silver paste for low temperature co-fired ceramics is described. The preparation method of the conductive silver paste for low temperature co-fired ceramics according to the embodiment of the present disclosure may include the following steps: S12. Mixing the mixed silver powder, the lead-free glass powder and the solvent in a mixer to obtain a first mixture.
[0038] S14. Adding graphene oxide, a surfactant, an organic additive and a thixotropic agent to the first mixture, and mixing to obtain a second mixture.
[0039] S16. Dispersing the second mixture using a high-speed disperser to obtain a third mixture.
[0040] S18. Grinding the third mixture multiple times on a three-roll mill to obtain a conductive silver paste for low temperature co-fired ceramics.
[0041] As described above, before step S12, a material preparation operation may be performed. Specifically, by weight percentage, 50 to 85 parts of mixed silver powder, 1 to 10 parts of lead-free glass powder, 1 to 5 parts of graphene oxide, 20 to 30 parts of solvent, 0.1 to 2 parts of surfactant, 1 to 3 parts of organic additives, and 0.3 to 2 parts of thixotropic agent may be taken.
[0042] The fineness of the silver paste prepared based on steps S12 to S18 can be controlled to be below 9 μm, the viscosity is 80 Pa·S to 360 Pa·S, and the sintering temperature is 650°C to 970°C.
[0043] Exemplary embodiments of the present disclosure are described below by way of examples.
[0044] Example 1 First, according to weight percentage, 70 parts of mixed silver powder, 3 parts of lead-free glass powder, 2 parts of graphene oxide, 20 parts of solvent, 0.2 parts of surfactant, 1 part of organic additive, and 0.3 parts of thixotropic agent are prepared.
[0045] The mixed silver powder includes 20% of spherical nano silver powder (D50=300nm), 20% of the first flaky silver powder (D50=5μm), and 60% of the second flaky silver powder (D50=10μm).
[0046] Next, the mixed silver powder, lead-free glass powder and solvent are fully mixed in a mixer, and then graphene oxide, surfactant, organic additive and thixotropic agent are added in sequence. After being fully mixed, a high-speed disperser is used for high-speed dispersion.
[0047] Then, the conductive silver paste for low temperature co-fired ceramics is obtained by rolling the product on a three-roll mill until the fineness is less than 9 μm.
[0048] Example 2 First, according to weight percentage, 70 parts of mixed silver powder, 3 parts of lead-free glass powder, 2 parts of graphene oxide, 20 parts of solvent, 0.2 parts of surfactant, 1 part of organic additive, and 0.3 parts of thixotropic agent are prepared.
[0049] The mixed silver powder includes 30% of spherical nano silver powder (D50=300nm), 20% of the first flaky silver powder (D50=5μm), and 50% of the second flaky silver powder (D50=10μm).
[0050] Next, the mixed silver powder, lead-free glass powder and solvent are fully mixed in a mixer, and then graphene oxide, surfactant, organic additive and thixotropic agent are added in sequence. After being fully mixed, a high-speed disperser is used for high-speed dispersion.
[0051] Then, the conductive silver paste for low temperature co-fired ceramics is obtained by rolling the product on a three-roll mill until the fineness is less than 9 μm.
[0052] Example 3 First, according to weight percentage, 70 parts of mixed silver powder, 3 parts of lead-free glass powder, 2 parts of graphene oxide, 20 parts of solvent, 0.2 parts of surfactant, 1 part of organic additive, and 0.3 parts of thixotropic agent are prepared.
[0053] The mixed silver powder includes 30% of spherical nano silver powder (D50=300nm), 30% of the first flaky silver powder (D50=5μm), and 40% of the second flaky silver powder (D50=10μm).
[0054] Next, the mixed silver powder, lead-free glass powder and solvent are fully mixed in a mixer, and then graphene oxide, surfactant, organic additive and thixotropic agent are added in sequence. After being fully mixed, a high-speed disperser is used for high-speed dispersion.
[0055] Then, the conductive silver paste for low temperature co-fired ceramics is obtained by rolling the product on a three-roll mill until the fineness is less than 9 μm.
[0056] The conductive silver paste prepared in Examples 1, 2 and 3 was used for grid printing. The process of grid printing is as follows: First, clean the surface of the alumina ceramic substrate to remove pollutants such as dust and grease to ensure that the silver paste can be evenly coated.
[0057] Next, the prepared conductive silver paste is fully stirred to ensure that the silver particles are evenly dispersed to avoid precipitation.
[0058] Then, the conductive silver paste is evenly coated on the surface of the alumina ceramic substrate by screen printing with a mesh size of 300, wherein the screen printing area is, for example, 1 cm×1 cm.
[0059] After printing, it can be placed in a blast drying oven, set the temperature to 200°C, and bake for 10 minutes. After drying, high-temperature curing is performed, the temperature is set to 800°C, and the baking time is 30 to 60 minutes.
[0060] After curing the conductive silver paste for low temperature co-fired ceramics prepared in the above Examples 1, 2 and 3, a silver film for testing was obtained. The silver film was tested for performance, including fineness, viscosity, square resistance, hardness, adhesion, etc. The test results are shown in Table 1: Table 1
[0061] As shown in the results in the table, the conductive silver paste of the embodiment of the present disclosure has higher quality.
[0062] In detail, Example 1 uses a mixed silver powder with a ratio of 20:20:60 of spherical nano silver powder, first flaky silver powder, and second flaky silver powder to prepare a conductive silver paste. Example 2 uses a mixed silver powder with a ratio of 30:20:50 of spherical nano silver powder, first flaky silver powder, and second flaky silver powder to prepare a conductive silver paste. Example 3 uses a mixed silver powder with a ratio of 30:30:40 of spherical nano silver powder, first flaky silver powder, and second flaky silver powder to prepare a conductive silver paste. Combined with their respective particle sizes, the resistivity of the conductive paste prepared after the ratio of nano silver powder to micron silver powder is increased is lower, and the conductive performance is further greatly improved.
[0063] refer to Figure 2 , Figure 3 and Figure 4 The SEM images of the silver films of Examples 1, 2 and 3 are shown respectively, and the SEM characterization of the printed surface after curing is performed. It can be seen that some substances are relatively floated on the surface of Examples 1 and 2, indicating that the silver powder is sintered relatively loosely, while no substances are floated on the surface of Example 3, and the sintering is relatively denser.
[0064] The conductive silver paste prepared by the embodiment scheme of the present disclosure has high sintering density, which improves the solderability and plating performance of the surface silver. In addition, compared with embodiments 1 and 2, the conductive silver paste obtained by the configuration scheme of embodiment 3 of the present disclosure is of better quality. The present disclosure can also lay the foundation for achieving the densification of the surface metal layer by optimizing the amount of silver powder with different particle sizes in the silver powder with a mass ratio. The silver powder with an optimized mass ratio is adopted to achieve a better surface densification effect.
[0065] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0066] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0067] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.
[0068] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A conductive silver paste for low temperature co-fired ceramics, characterized in that: The conductive silver paste comprises the following components: mixed silver powder, lead-free glass powder, graphene oxide, solvent, surfactant, organic additive, and thixotropic agent; Wherein, the mixed silver powder includes spherical nano silver powder and flaky silver powder, the mass ratio of the spherical nano silver powder to the flaky silver powder is 1:1 to 1:6, the flaky silver powder includes a first flaky silver powder and a second flaky silver powder, the particle size of the first flaky silver powder is smaller than the particle size of the second flaky silver powder, and the weight ratio of the first flaky silver powder is greater than the weight ratio of the second flaky silver powder.
2. The conductive silver paste for low temperature co-fired ceramics according to claim 1, characterized in that: In parts by weight, the mixed silver powder comprises 50 to 85 parts, the lead-free glass powder comprises 1 to 10 parts, the graphene oxide comprises 1 to 5 parts, the solvent comprises 20 to 30 parts, the surfactant comprises 0.1 to 2 parts, the organic additive comprises 1 to 3 parts, and the thixotropic agent comprises 0.3 to 2 parts.
3. The conductive silver paste for low temperature co-fired ceramics according to claim 1, characterized in that: In terms of weight percentage, the lead-free glass powder includes 52% to 55% SiO2, 3% to 8% Al2O3, 18% to 20% B2O3, 5% to 7% Na2O, 1% to 2% K2O, 2% to 3% ZnO, 2% to 4% BaO, 5% to 6% CaO, and 3% to 4% MgO.
4. The conductive silver paste for low temperature co-fired ceramics according to claim 1, characterized in that: The solvent is formed by mixing a polymer resin and an organic carrier, and the mass ratio of the polymer resin to the organic carrier is 2:8 to 4:
6.
5. The conductive silver paste for low temperature co-fired ceramics according to claim 4, characterized in that: The polymer resin includes one or more of ethyl cellulose, DBE, epoxy resin, vinyl resin, and polyurethane resin; The organic carrier includes one or more of terpineol, ethylene glycol, and 3-methoxy-3-methylbutyl acetate.
6. The conductive silver paste for low temperature co-fired ceramics according to claim 1, characterized in that: The surfactant includes sorbitan trioleate or tributyl phosphate.
7. The conductive silver paste for low temperature co-fired ceramics according to claim 1, characterized in that: The organic additive is formed by mixing a dispersant, a leveling agent and a defoaming agent, and the mass ratio of the dispersant, the leveling agent and the defoaming agent is 0.8:0.5:0.9 to 1:1:
1.
8. The conductive silver paste for low temperature co-fired ceramics according to claim 7, characterized in that: The dispersant includes one or more of sodium lauryl sulfate, polyethylene glycol, and oleic acid; The leveling agent includes one or more of silane coupling agent, diacetone alcohol, and polymethylphenylsiloxane; The defoaming agent includes modified polysiloxane or organosilicon defoaming agent.
9. The conductive silver paste for low temperature co-fired ceramics according to claim 1, characterized in that: The thixotropic agent includes one or more of 1-methyl-2-pyrrolidone, 2-methylpyrrolidone, and gas-phase nano-silicon dioxide.
10. A method for preparing a conductive silver paste for low temperature co-fired ceramics, characterized in that: The conductive silver paste for low temperature co-fired ceramics is the conductive silver paste according to any one of claims 1 to 9; wherein the preparation method comprises: Mixing the mixed silver powder, the lead-free glass powder and the solvent in a mixer to obtain a first mixture; adding graphene oxide, a surfactant, an organic additive and a thixotropic agent to the first mixture, and mixing them to obtain a second mixture; Dispersing the second mixture using a high-speed disperser to obtain a third mixture; The third mixture is ground multiple times on a three-roll mill to obtain the conductive silver paste for low-temperature co-fired ceramics.
Citation Information
Patent Citations
Crystal ceramic thick-film electric heating device and manufacturing method thereof
CN102791049A
High-strength low-temperature-sintering glass ceramic bonding agent and preparation method thereof
CN107160296A
High-performance sintered conductive silver paste and preparation method and sintering method thereof
CN108735339A
Low-temperature co-fired ceramic internal conductive silver paste and preparation method thereof
CN112614608A
Lead-free bismuth-free high-performance dielectric paste
CN114049986A